(untitled) (The Research of Medical Science Review, 2025)
Background: Contraceptive usage is a significant element of reproductive health. Despite putting so many efforts to control population growth and family planning in developing countries, the use of contraceptive remains suboptimal particularly in low- and middle-income families. Considering the demographic factors affecting contraceptive usage to initiate targeted interventions and bring the positive outcome in family planning services. Objective: To assess the role of socioeconomic status on the contraceptive's usage amongst married women in Karachi, Pakistan. Method: An analytical cross-sectional study conducted among 400 married women under reproductive age group (15-49 years old) belong to low- and middle- income households in two different areas of Karachi Pakistan. Participants were recruited via non-probability convenient sampling. Structured questionnaire tool was employed for data collection. For analysis, SPSS version 22 was used. The descriptive data was calculated through frequency and percentages whereas the inferential data was retrieved by using chi-square test. Results: The study results showed that around 49%of the participants were using family planning methods. The socio-demographic characteristics such as area of residence, number of children, employment status, monthly income, awareness and current usage of family planning methods were significantly associated with the family planning utilization. The level of education and age did not have impact of family planning utilization. Conclusion: In conclusion, our study sheds light on geographic location, economic conditions, family dynamics, employment status, and awareness levels are key determinants of family planning utilization. These findings underscore the importance of targeted interventions that address these factors to enhance the uptake of family planning methods. Conversely, factors like education level, age, and decisions on future pregnancies do not significantly influence FP utilization, suggesting that these areas might require different approaches or are less critical in the context studied.